Brittle-ductile transition of amorphous polymers via high temperature programming - Pek, Jia Xi (Nanyang Technological University, 2021)
High-temperature processing had been done throughout history on materials such as metals and clay, and now on modern materials like polymers too. These processing came in the form of annealing, tempering, etc. Such processes have been known to strengthen and improve the materials’ ductility, among other things, long before studies have been done to prove them. What these processes have in common is that they change the physical and sometimes even the chemical properties of the material which in turn changes their mechanical or electrical properties. What this report will be investigating is another form of high temperature programming known as prestretching. The materials that are chosen to be the subjects are commercial poly(methyl methacrylate) (PMMA) and polycarbonate (PC). Prestretching refers to having a sample heated up to around 160 ℃ and then stretch it while at that temperature. Consequently, this will result in prestrain — also known as residue strain — within the programmed sample. Similar to other types of high-temperature programming, this should change the mechanical properties of PMMA and PC, which is the motivation of this report.